2020
DOI: 10.1002/oby.22978
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Ovarian Suppression in Premenopausal Women: No Change in Free‐Living Energy Expenditure

Abstract: Objective The purpose of this study was to determine whether suppression of ovarian function (gonadotropin‐releasing hormone agonist [GnRHAG]) for 24 weeks in premenopausal women approaching menopause causes changes in body composition and a decline in free‐living physical activity energy expenditure (PAEE) and whether endurance exercise training attenuates the changes. Methods Premenopausal women who were approaching menopause (mean [SD]: age 46 [3] years, BMI 26.3 [4.8] kg/m2) were randomized to 24 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…Although free-living TDEE (as measured by doubly labeled water) decreased 93 kcal/day and RMR decreased 59 kcal/day in the GnRH agonist group, these differences were nonsignificant within or between groups. There were also no significant alterations in physical activity energy expenditure, although these results may be due to large variability in energy expenditure components observed in this study [75]. In sum, it appears that reduced estrogen may decrease RMR and TDEE in confined settings; however, these changes may not translate to free-living settings as evidenced by results from doubly labeled water.…”
Section: Estrogen and Total Daily Energy Expenditurecontrasting
confidence: 55%
See 1 more Smart Citation
“…Although free-living TDEE (as measured by doubly labeled water) decreased 93 kcal/day and RMR decreased 59 kcal/day in the GnRH agonist group, these differences were nonsignificant within or between groups. There were also no significant alterations in physical activity energy expenditure, although these results may be due to large variability in energy expenditure components observed in this study [75]. In sum, it appears that reduced estrogen may decrease RMR and TDEE in confined settings; however, these changes may not translate to free-living settings as evidenced by results from doubly labeled water.…”
Section: Estrogen and Total Daily Energy Expenditurecontrasting
confidence: 55%
“…Furthermore, 24 h EE measured via whole room indirect calorimetry was also reduced by estrogen suppression (~100-110 kcal/day), but was not prevented by estradiol addback [74]. A similar follow-up study was conducted in which premenopausal women were randomized to 24 weeks of GnRH agonist (N = 14), GnRH agonist + aerobic exercise (N = 11), or placebo (N = 9) [75]. Although free-living TDEE (as measured by doubly labeled water) decreased 93 kcal/day and RMR decreased 59 kcal/day in the GnRH agonist group, these differences were nonsignificant within or between groups.…”
Section: Estrogen and Total Daily Energy Expenditurementioning
confidence: 99%
“…Our findings concur with previous research that menopausal status and sex hormone levels do not robustly determine REE adj during midlife. Although ovarian hormone suppression studies in premenopausal women have shown some yet not fully convincing evidence of a REE adj decline ( 40 , 41 ), MHT interventions show no clear effect on REE in postmenopause ( 15 , 17 , 18 ). In the present study, the MHT users had even lower REE than postmenopausal women who did not use MHT after adjusting for FFM, FM, and age.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings concur with previous research that menopausal status and sex hormone levels do not robustly determine REE adj during midlife. Although ovarian hormone suppression studies in premenopausal women have shown some yet not fully convincing evidence of a REE adj decline (36,37), MHT interventions show no clear effect on REE in postmenopause (15,17,18). In the present study, the MHT users had even lower REE than postmenopausal women who did not use MHT after adjusting for FFM, FM and age.…”
Section: Discussionmentioning
confidence: 97%
“…Our finding that menopausal status or sex hormone concentrations did not explain REEadj in midlife broadly agrees with previous studies. Long-term ovarian hormone suppression studies in premenopausal women have shown some yet not fully convincing evidence of a REEadj decline (36,37), while MHT has no apparent effect on REE in postmenopause (15,17,18). Observational evidence suggests that menopause has a negligible impact on REEadj.…”
Section: Discussionmentioning
confidence: 99%